Literacy Activities in the Go Green Program to Increase Environmental Awareness among Elementary School Students - Mohamad Husein Nurullah; Aliet Noorhayati Sutisno; Fanny Septiany Rahayu (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the effectiveness of literacy activities in the Go Green program in improving elementary school students’ environmental awareness, which includes cognitive, affective, and conative dimensions. The research subjects were 40 fifth-grade students (class V.B) at SDN 1 Arjawinangun. The program was implemented from February to June 2025 with literacy activities focusing on greening, waste management, reduction of single-use plastics, and energy and water conservation. The study employed a one-group pretest–posttest design using questionnaires before and after the program, accompanied by observations to capture students’ behavior during the activities. The results of the paired sample t-test indicated a significant increase in students’ environmental awareness, with posttest scores on average 9.75 points higher than pretest scores (t = -18.004; p < 0.001). Simple regression analysis revealed that literacy activities in the Go Green program had a positive and significant effect on improving overall environmental awareness. Meanwhile, multiple regression analysis showed that the four literacy activities contributed differently to students’ cognitive, affective, and conative dimensions. These findings demonstrate a strong effect size. However, this study is limited by the use of a one-group design, reliance on self-reported measures, and restricted generalization since it involved only one class from a single school.